Assistência a doentes com infecção pelo vírus da imunodeficiência humana: experiência num Serviço de Medicina Interna - Lucas, Margarida (1994)
We report our experience on HIV infection in the context of an Internal Medicine Department in a Central Hospital, regarding both out patient and inpatient medical management. The clinical and epidemiological characteristics of the 54 patients (HIV1 - 46 and HIV2 - 8) as well as some diagnostic aspects of the opportunistic infections and of the antiviral therapy options are presented. We analyse the evolution of the patients throughout a medium follow-up period of two and halfyears as well as the significant impact in terms of hospital admissions. Emphasis is given to the motivation and collaboration of all the health professionals to face the difficult clinical problems of these patients in the context of an Internal Medicine Unit. Finally the role of the Internist in the health care of patients with HIV infection is discussed and we argue in favour of a direct and continuous involvement of these specialists in all stages of the natural history of the disease.